The Management of Foreign Language Development in an Islamic Boarding School - Nurmalina; Rusmiati; Musdalifah (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2023)
The mastery of foreign languages, especially English and Arabic. is one of the educational goals in most pesantrens in Aceh. This study aimed to find the management of foreign language development along with its supporting and hindering factors in one of pesantrens in Aceh Tengah using a descriptive qualitative approach. The data collection technique applied was interview, and the subjects were the leaders, teachers, and the students. This study delved into the four functions of management: planning, organizing, actuating, and controlling. The result of the investigation showed some plannings of the foreign language development management, i.e., holding a meeting at the beginning of the semester, selecting the language coordinator, and devising methods and techniques language development program. Next, organizing included forming the structure of the dayah organization, students’ organization, and administrator in language department. In addition, actuating in the language development was implemented in direct method and control. Both applied muhadharah (speech), muhadatsah (conversation), mufradat (vocabulary), listening, watching movie, and studying kitab kuning (yellow book). Lastly, controlling was executed by holding the meeting of the staffs’ main task result either at the end of every month or semester. This phase was done by language coordinator through language administrators. Then, the teachers (ustaz and ustazah) controlled by walking around and worked together with the jasusah (secret agent). Furthermore, the supporting factors of language development included the existing facilities and infrastructure, qualified teaching staff, and students’ high learning motivation. While the hindering factors were the lack of teaching staff in English, the lack of motivation from the leaders, and the lack of students’ interest in participating language development process.